Title: Understanding a Low Vitamin D State in the Context of COVID-19 - Walsh, James Bernard; McCartney, Daniel M.; Laird, Éamon; McCarroll, Kevin; Byrne, Declan G.; Healy, Martin; O’Shea, Paula M.; Kenny, Rose Anne; Faul, John L. (Frontiers in Pharmacology, 2022)
While a low vitamin D state has been associated with an increased risk of infection by SARS-CoV2 in addition to an increased severity of Covid-19, a causal role is not yet established. In order to gain a greater understanding of the potential link, an Irish cross disciplinary collaboration began to collate data regarding Covid-19 and vitamin D status in 2020. Here, the case against vitamin D status having an important role in Covid-19 is reviewed. Second, using the Bradford-Hill criteria, the observational and scientific data that support a causative role for low vitamin D status in the disease is outlined. Third, we describe the prevalence of low vitamin D status in Irish adults. The expert group concluded that reverse causality probably makes only a small contribution to the finding of low vitamin D states in the setting of Covid-19. In contrast, the case for a low vitamin D state being relevant in SARS-CoV2 infection is supported by Bradford Hill Criteria for causation. Decrements in vitamin D status are associated with a gradient of disease severity from asymptomatic, to symptomatic, to respiratory failure, to a requirement for mechanical ventilation, to death. The threshold between “low vitamin D” and “replete” can vary according to the disease studied, underscoring the complexities for determining definitive thresholds for therapeutic intervention. The design of vitamin D randomised controlled trials (RCTs) is notoriously problematic and these trials commonly fail for a number of behavioural and methodological reasons. Low vitamin D status is common throughout the adult life course with an age gradient in older adults and adults in institutions or with other high risk factors such as obesity, dark skin, poor sunlight exposure, diabetes, low socio economic status and institutionalisation. In Ireland, physiological vitamin D requirements for optimal immune function are considerably higher than those that can be achieved from food alone. A window exists in which a large number of adults would benefit from vitamin D supplementation because their low vitamin D state places their immune system in a vulnerable position. This is especially important during the current pandemic and is particularly pertinent to older adults.